2017
DOI: 10.1128/genomea.00214-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Isolates of Colletotrichum lindemuthianum , the Causal Agent of Anthracnose in Common Beans

Abstract: Colletotrichum lindemuthianum is the causal agent of anthracnose in common beans, one of the main limiting factors of their culture. Here, we report for the first time, to our knowledge, a draft of the complete genome sequences of two isolates belonging to 83.501 and 89 A2 2-3 of C. lindemutuianum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Recently, the genomes of more than 20 Colletotrichum species have been sequenced ( O’Connell et al, 2012 ; Alkan et al, 2013 ; Gan et al, 2013 , 2016 , 2017 ; Baroncelli et al, 2014a , b , 2016 ; Hacquard et al, 2016 ; Han et al, 2016 ; Hiruma et al, 2016 ; Queiroz et al, 2017 ), revealing a tremendous diversity in genome architecture and gene content. While most of the studies focused on comparisons of distantly related lineages they also demonstrate the need for higher resolution taxonomic sampling in order to better understand the evolution of fungal genomes and the possible association with phenotypic characters such as host range, pathogenic lifestyle and reproductive strategy.…”
Section: The C Acutatum Species Complex As a Modementioning
confidence: 99%
“…Recently, the genomes of more than 20 Colletotrichum species have been sequenced ( O’Connell et al, 2012 ; Alkan et al, 2013 ; Gan et al, 2013 , 2016 , 2017 ; Baroncelli et al, 2014a , b , 2016 ; Hacquard et al, 2016 ; Han et al, 2016 ; Hiruma et al, 2016 ; Queiroz et al, 2017 ), revealing a tremendous diversity in genome architecture and gene content. While most of the studies focused on comparisons of distantly related lineages they also demonstrate the need for higher resolution taxonomic sampling in order to better understand the evolution of fungal genomes and the possible association with phenotypic characters such as host range, pathogenic lifestyle and reproductive strategy.…”
Section: The C Acutatum Species Complex As a Modementioning
confidence: 99%
“…Since hundreds of effector molecules were predicted in the recently released genomes of C. lindemuthianum (de Queiroz et al . 2017, 2018) and our optimized ATMT protocol will help in functional characterization of these effector molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of ‘omics age’ and adaptation of next generation sequencing technologies has resulted in the availability of the first draft genome of C. lindemuthianum (de Queiroz et al . 2017). A recent comparative effector repository study revealed a large set of diverse and unique effectors molecules in C. lindemuthianum (de Queiroz et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than ten genomes of the genus Colletotrichum have been sequenced to date [72][73][74][75][76]. Members of Colletotrichum belong to six independent species complexes that deploy various infection strategies, including biotrophic, necrotrophic, hemibiotrophic, and endophytic strategies, to derive nutrients from colonized monocotyledonous and dicotyledonous plants [7,19,74].…”
Section: Discussionmentioning
confidence: 99%